Capim-xaraés sob lotação contínua manejado em diferentes intensidades de pastejo - Ribeiro, Aline Mendes (2014)
The purpose of this study was to quantify the effect of different grazing intensities (25, 35, 45 and 55 cm sward heights) on the production characteristics, structural, morphogenetic and nutritional value in areas managed with xaraés grass (Brachiaria brizantha), and physical attributes of the soil, during the seasons. For the management of heights Nellore cattle were used, and managed under continuous stocking with variable stocking rate. The experimental area consisted of 12 paddocks of ha-1 each. Samples were taken every 28 days in order to estimate the production, accumulation rate and the morphological components of the forage. The nutritive value was determined in the fractions leaf blade and stem, and on the grazing plucked samples. The readings of light interception (IL) and leaf area index (LAI) were taken every 15 days. The tillers were counted every 28 days at fixed points of the pasture in order to estimate the population density of tillers (PDT). Sixty tillers per paddock were collected every 28 days to determine the average weight. The morphogenetic and structural characteristics were determined by evaluating 40 tillers per paddock, every three days for 28 days of each evaluation period. The randomized experimental design consisted of a subdivided plot with three replications. The soil physical properties (soil density - Sd - porosity and soil resistance to root penetration - RP -) were taken in February and June, through the methodologies described by Embrapa. The total forage mass ranged from 4510 to 8514 kg ha-1 of dry matter, being lower at 25 cm and greater at 45 cm. The mass of leaf blades increased linearly with canopy heights ranging from 1815 to 2658 kg ha-1 of dry matter. There were higher rates of total accumulation and leaf blades at higher pastures, ranging from 20.37 to 96.86 kg ha-1 of dry matter. Percentages of leaf blades were higher in late spring, ranging from 33.15% to 46.97%, in lower pastures. In summer, the percentages of stem were higher for thatched swards grazed at 55 cm (42.19%). There was a reduction in the ratio leaf blade and stem in higher pastures. The percentages of dead material increased linearly according to sward height and ranged from 26.20 to 47.62% among the evaluated heights. In general, higher nutritional value, with higher concentrations of crude protein (122 g kg-1) and in- vitro digestibility of dry matter (66 g kg-1) in swards grazed, were lower in the fall. Higher concentrations of neutral detergent fiber (72 g kg-1) and acid detergent fiber (36 g kg-1) was observed in the summer, with increasing height of the pastures. IL ranged from 88% to 95% and the IAF from four to six between the heights evaluated, relating positively to canopy height. The PDT baseline was lower at greater height (524 tillers/m2). Plant height was increased linearly thus increasing the average mass per tiller, which ranged and 1.4 - 2.4 g/tiller. The elongation rate and leaf appearance decreased linearly with increasing height and higher values in late spring and summer. Rates of stem elongation and leaf senescence were higher at greater grazing height. The numbers of green leaves and expansion were higher in summer and late spring, with lower height. The final leaf length positively related to canopy height, with higher values in late spring and summer. There was an increased soil in July, as compared to February (1.64 Mg m-3). There was no difference in the values of soil porosity; however, there was a tendency for lower values of macro porosity in the treatments evaluated in July. Conditions of soil moisture for the collection periods differed, and in July the soil showed higher moisture (10.97%) compared to February (6.45%). However, between depths collected and evaluated heights there was little variation. In February, almost all values of penetration resistance were superior to two MPa, a value adopted as more critical. In the interval between depths of 0.20 m to 0.40 m, there was the occurrence of an increase in resistance to penetration. By using continuous stocking between 35 and 45 cm on xaraés grass, depending on the objectives of production, data revealed that the characteristics of the pasture were influenced by the seasons and by grazing height.